2013
DOI: 10.1016/j.pain.2012.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Chronic opioid use is associated with increased DNA methylation correlating with increased clinical pain

Abstract: Environmentally caused changes in chromosomes that do not alter the DNA sequence but cause phenotypic changes by altering gene transcription are summarized as epigenetics. A major epigenetic mechanism is methylation or demethylation at CpG-rich DNA islands. DNA methylation triggered by drugs has largely unexplored therapeutic consequences. Here we report increased methylation at a CpG rich island in the OPRM1 gene coding for μ-opioid receptors and at a global methylation site (LINE-1) in leukocytes of methadon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
140
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(148 citation statements)
references
References 63 publications
7
140
1
Order By: Relevance
“…Epigenetic mechanisms are suggested to be responsible for this phenomenon (38,39). Although investigations of the effects of these types of opiates are scarce, some recent studies in animal models have shown that the offspring of parents with a background of morphine use demonstrate differences in the expression pattern of opioid receptors in different brain areas (36).…”
Section: Discussionmentioning
confidence: 99%
“…Epigenetic mechanisms are suggested to be responsible for this phenomenon (38,39). Although investigations of the effects of these types of opiates are scarce, some recent studies in animal models have shown that the offspring of parents with a background of morphine use demonstrate differences in the expression pattern of opioid receptors in different brain areas (36).…”
Section: Discussionmentioning
confidence: 99%
“…Opiate receptors ↔ development (Hwang et al, 2007) Local anaesthetics ↓ methylation (Lirk et al, 2012(Lirk et al, , 2014 Opiates ↑ methylation (Doehring et al, 2013) Opiate-induced hyperalgesia (Doehring et al, 2013) ↓ MCP3 expression → pain (Imai et al, 2013) ↓ GAD65 expression → pain (Zhang et al, 2013) Prefrontal cortex methylation (Tajerian et al, 2013) TRPA1 methylation ↔ pain (Bell et al, 2014) Transcriptome in inflammation (Bais et al, 2009) Transcriptome in healing (Kruidenier et al, 2012;Barnes et al, 2013;Belkina et al, 2013) Cell migration/prolif, angiogenesis (Rafehi et al, 2011) Heritable response to injury (Zeybel et al, 2012) Wound healing inflammation…”
Section: Painmentioning
confidence: 99%
“…In humans, increased DNA methylation levels in peripheral blood leukocytes have been linked to the severity of chronic pain in patients on long-term treatment using potent opioids (Doehring et al, 2013). A recent investigation in monozygotic twins found that the degree of heat pain sensitivity correlated with the methylation status of the gene that encodes the TRPA-1 ion channel (Bell et al, 2014).…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…63 Interestingly, this effect is the opposite compared with long-term opioid intake, which leads to hypermethylation. 64 …”
Section: Direct Effects On Cancer Cells: Inflammatory Signaling Migrmentioning
confidence: 99%